A review of helium resources and development - Zhongjun Hu; Jingyu Li (Natural Gas Industry B, 2025)
Due to its unique properties, helium is critical in scientific research and industrial innovation, particularly in cryogenics; however, its scarcity necessitates efficient resource utilization. Through a review of the historical development of the helium industry, this study comprehensively evaluates the value, sources, production methods, supply dynamics, and sustainability challenges of helium. The processes and mechanisms of helium enrichment, along with effective exploration methods, are systematically analyzed here. We recommend focusing on the development of technologies for helium preservation, recovery, and extraction, particularly the extraction technology for helium-poor fields. Market analysis indicates that no imminent crisis in the global helium supply is expected before 2060. Thus, enhancing helium resource protection technologies is essential to improve its economic utilization and management while providing a timely reference for the scientific community.